Tradition Bakar Batu: Binding Papuan Diaspora Identity in Urban Areas: A Case Study of Jakarta, Bogor, Depok, and Bekasi - Donald Kasenda (Universitas KH. Abdul Chalim Mojokerto, 2025)
The tradition Bakar Batu (stone burning) is a cultural ritual that has a deep meaning for the Papuan people, not only as a traditional way of cooking but also as a unifying medium and cultural identity guardian. This study aims to analyze how the tradition of bakar batu plays a role in maintaining the cultural identity of Papuan migrants in urban areas such as Jakarta, Bogor, Depok, and Bekasi, (Jabodebek), and examine the dynamics of the implementation of the tradition in the urban context. The research uses a qualitative approach with ethnographic methods, involving participatory observation and in-depth interviews with Papuan migrants. The results show that the tradition of stone burning functions as: (1) binding solidarity among communities in the diaspora, (2) a means of intergenerational transmission of cultural values, (3) a symbol of resistance to the erosion of cultural identity, and (4) a medium for negotiating identity in urban space. The adaptation of traditional implementation in the urban context reflects the cultural resilience of Papuan migrants in maintaining their cultural identity. This research contributes to the understanding of the role of tradition in maintaining social cohesion and cultural identity of urban communities.